أثر القيادة الإدارية على تحسين جودة الأداء في الجامعات الليبية – دراسة ميدانية في جامعة الجفارة (Comprehensive Journal of Science, 2025)
This study aimed to investigate the impact of administrative leadership on improving performance quality in Libyan universities, with a field application at Al-Jafara University, a descriptive-analytical approach was used, based on a questionnaire of four dimensions: leadership styles, leadership skills, institutional performance stability, and academic and administrative performance quality, the tool was administered to a purposive sample of 60 respondents including administrative leaders, faculty members, and administrative staff, the results revealed a strong positive correlation between administrative leadership and performance quality, with a clear impact of participative styles and communication and problem-solving skills on enhancing quality levels, no statistically significant differences appeared according to gender, whereas significant differences were found according to years of experience in favor of more experienced staff, the findings also indicated that limited resources, work overload, and weak administrative coordination are key challenges facing university leadership.
Keywords: Administrative leadership, quality of performance, Libyan universities, Al-Jafara University, participative leadership, institutional performance stability